Modélisation de la structure cristalline d'un nouveau composé à propriétés optique non linéaires - BENHALIMA, Nadia (My University, 2013)
We report here the crystal structure of (Z)-5-(4-nitro-benzyliden)-3-N(2-ethoxyphenyl)-2-thioxo-thiazolidin-4-one (ARNO) compound. The crystal structure has been determined by X-ray diffraction. The compound crystallizes in the triclinic system with space group and cell parameters: a = 9.1289(19) Å, b = 9.3717(7) Å, c = 12.136(3) Å, α = 102.133 (11) °, β = 90.99(2) °, γ = 117.165(9) °, V = 895.4(3) Å3 and Z = 2. The structure has been refined to a final R = 0.05 for 2591 observed reflections. The refined structure was found to be significantly non planar. The molecule exhibits intermolecular bond type C–H…O and C–H…S Dipole moment, polarizability, and first-order hyperpolarizability of ARNO and thiazolidinone derivatives have been investigated using ab initio and density functional theory calculations. In general, the first hyperpolarizability is dependent on the choice of method and basis set. The study reveals that the ARNO and thiazolidinone derivatives have large β values hence in general may have potential applications in the development of non-linear optical materials.